Reabilitas Daya Dukung Pondasi Tiang Bor Berdasarkan Formula Reese & Wright dan Usulan Load Resistance Factor Design dalam Perencanaan Pondasi Tiang Bor Studi Kasus Proyek Jakarta - Lastiasih, Yudhi; Irsyam, Masyhur; Sidi, Indra Djati; Toha, FX (MEDIA KOMUNIKASI TEKNIK SIPIL, 2013)
Design bored pile foundation often use formulae of Reese and wright (1977) on projects heild in Jakarta. The safety factor often use on the design foundation on project in Jakarta are generally 2 or 3. By using advance First Order Liability Method to analysis design foundation, the result showed that the design was very conservative. Proven by the safety index for this design is 2.68 where’s the equivalent of failure probably 3.72 x 10-3, this result is less than requirement of failure probability 1 x 10-2. Lastiasih (2012) propose the use of multiple safety factors by applying Load Resistance Factor Design (LRFD) in accordance with the design of building age so as not to use single safety factor again. Further more the design of bored pile foundation become more efficient.